Mytilus galloprovincialis fast growing phenotypes under different restrictive feeding conditions: Fast feeders and energy savers. (September 2018) - Prieto, D.; Urrutxurtu, I.; Navarro, E.; Urrutia, M.B.; Ibarrola, I.
Abstract: The present study aims to test if the environmental conditions prevailing during the growing period can determine the physiological profiles of specimens differentiated as fast (F) or slow (S) growers in the mussel Mytilus galloprovincialis . We reared mussel spats in the laboratory under two different conditions. In Treatment I (continuous feeding during discontinuous immersion), two mussel groups were submitted to a daily air exposure of 8 h and fed continuously during immersion-time, with either high-quality food dosed below the pseudofaeces threshold (BP group) or low organic content food dosed above the pseudofaeces threshold (AP group). In Treatment II (discontinuous feeding during continuous immersion), mussels were continuously immersed but fed only 1 day per week (RC group). Mussels were reared for 7 and 11 months (time required for size-differentiation) in Treatments I and II, respectively, and the smallest and largest individuals from each group were selected as S and F specimens. A series of feeding experiments (with different food quality, food ration and under continuous food supply) were performed to analyse the physiological performance of selected F and S mussels. In Treatment I, no significant differences were found in the metabolic rates between F and S mussels, and the faster growth rate of F-mussels resulted from their capacity to display higher clearance-ingestion rates and pre-ingestive selections. The physiological basis of growth rate differences between F and S mussels were found to be the same in mussels reared with diets below or above a pseudofaeces threshold (FBP, FAP, SBP and SAP ). In contrast, the mussels from Treatment II had no significant differences in the feeding rates between FRC and SRC mussels. However, F individuals were found to have a 33% lower standard metabolic rate, indicating that fast growth under severe feeding restriction stemmed from a higher capacity of F-mussels to save energy during long periods of starvation. Despite the differences in the physiological basis explaining fast growth between the two treatments, F-mussels were found to possess significantly higher gill-surface area in both cases. It is thus concluded that endogenous factors affecting the gill-surface area play a major role in determining inter-individual growth rate differences in the mussel, Mytilus galloprovincialis . Highlights: Rearing environment determines the energetic basis for fast growing in mussels. Under continuous feeding conditions fast feeding mussels arise as fast growers. Under food restricted conditions energy saving mussels arise as fast growers. Fast growing mussels show enhanced capacity for particle sorting. Higher gill surface area is an innate trait of fast growing individuals.